Functional health performance outcomes of compliance to home instruction program after myocardial infarction - Balabagno, Araceli O.
During the transition from hospital to the home setting, clients had expressed need for care because of the overwhelming experience brought about by the physical, physiologic, psychosocial and emotional effects of myocardial infarction.~~~~The home instruction progrm and scheduled home visits were prescribed to address the client's needs. The intervention was based on the concepts of interaction, goal setting and information support. By increasing the quality of interaction between the client, the nurse and significant others, successful adjustment and recovery will be attained and functional health performance will improve. Functional health performance was defined in terms of the weighted scores of quality of life, perceived exertion to walking and treadmill exercise test scores.